Identifikasi Potensi Hazard pada Pengunjung Xplore62 Menggunakan Metode Hazop dan HIRADC - Nasution, Arya Cahya; Abrar, Hikmal; Zulfah, Nur Saumi Indana; Nanda, Rahmat Gian; Purwandari, Aprilia Tri (Universitas Al Azhar Indonesia, 2024)
Occupational Safety and Health is an issue that is currently attracting a lot of attention from various organizations because it covers issues from the human aspect, economic costs and benefits, legal aspects, accountability and the image of the organization itself. In this research, efforts to prevent work accidents will be carried out using the Hazard Identification Risk Assessment and Detection Control (HIRADC) method. This research aims to determine and analyze hazard identification using the HAZOP method, determine risk control, and determine risk assessment for occupational safety and health. Hazard identification is carried out with the aim of determining the potential danger of a material, tool, or system (Department of Occupational Safety and Health. HAZOP is a systematic safety study, based on a systemic approach towards safety assessment and the process of operating complex equipment, or production processes. Based on the results of the hazard identification carried out on namely slipping, falling, being hit by a tree, etc. Risk control efforts that will be carried out in give danger signs, wear PPE and so on.